Kualitas Mikroorganisme Lokal Dari Keong Mas Dengan Berbagai Jumlah Bahan Yang berbeda - Zainal Abidin; Rusmini; Riama Rita Manullang; Daryono (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Golden snail is a snail which is commonly found in rice fields which can cause damage to rice plants. The golden snail is known as a pest of rice plants because it can damage thousands of hectares of rice seedlings at an early age in a short period of time but will be beneficial if it is managed as a microorganism. Local microorganisms are microorganisms used as starters in the manufacture of solid organic fertilizers and liquid fertilizers as well as fast growing decomposers in agricultural systems. The purpose of this study was to determine the quality of local microorganisms in producing bioactivators from various amounts of different ingredients in the golden snail. This research was conducted in four locations, namely the Agronomy Laboratory of the Samarinda State Agricultural Polytechnic (manufacturing bioactivators), the Production Laboratory of the Samarinda State Agricultural Polytechnic (composting), and at Sucopindo (nutrient analysis). This research used three treatments including golden snail bioactivator I (A1), golden snail bioactivator II (A2), and golden snail bioactivator III (A3). Based on the results of the study, it can be concluded that treatment A3 (Keong Mas III Bioactivator) gave the best results for the parameters of temperature, color, odor and C-organic local microorganism (MOL) for the golden snail, while treatment A1 (Bioactivator Keong Mas I) gave the best results for the parameters Ph.